2022
DOI: 10.3389/fpls.2022.879182
|View full text |Cite
|
Sign up to set email alerts
|

Chile Pepper (Capsicum) Breeding and Improvement in the “Multi-Omics” Era

Abstract: Chile pepper (Capsicum spp.) is a major culinary, medicinal, and economic crop in most areas of the world. For more than hundreds of years, chile peppers have “defined” the state of New Mexico, USA. The official state question, “Red or Green?” refers to the preference for either red or the green stage of chile pepper, respectively, reflects the value of these important commodities. The presence of major diseases, low yields, decreased acreages, and costs associated with manual labor limit production in all gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 158 publications
(160 reference statements)
0
11
0
Order By: Relevance
“…outcrossing) species 10 , however, commercial pepper varieties are managed and bred as fully autogamous 11 . Hybridization between pepper varieties or species was generally used for fundamental research to identify genes of interest, but more recently it has become commonplace as a breeding tool per se 12 . Hybridization breeding allows the combination of dominantly inherited traits, including disease resistance and agronomic traits 13 .…”
Section: Introductionmentioning
confidence: 99%
“…outcrossing) species 10 , however, commercial pepper varieties are managed and bred as fully autogamous 11 . Hybridization between pepper varieties or species was generally used for fundamental research to identify genes of interest, but more recently it has become commonplace as a breeding tool per se 12 . Hybridization breeding allows the combination of dominantly inherited traits, including disease resistance and agronomic traits 13 .…”
Section: Introductionmentioning
confidence: 99%
“…It might also be necessary to survey the metabolite compositions of cultivated and wild relatives of the chile pepper for a more robust foundation for targeted genomic breeding strategies [ 39 ]. Altogether, ‘multi-omics’ tools (e.g., genomics + metabolomics) can help plant breeders perform informed breeding and selection decisions for the development of cultivars with improved nutritional quality traits [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review paper highlighted the significance of available multi-omics such as genomics, transcriptomics, metabolomics, proteomics, epigenomics, phenomics, speed breeding, agricultural robotics and panomics data on capsicum breeding and suggested the integration of these multi-omics would advance the understanding of the genetic basis for the various traits of the chilli and help quickly develop the chilli hybrids with the desired traits [31]. Moreover, acquiring the knowledge on chilli genetic diversity is paramount in developing new varieties, therefore, in China, a recent study was aimed on analysis of genetic diversity between 94 local landraces and 85 current breeding lines by evaluating 22 qualitative traits, 13 quantitative traits and 27 molecular markers, and found that mean values of Gene Diversity index and Polymorphism Information content of local landraces were higher than breeding lines, hence recommended for interspecific crosses between landraces and breeding lines to expand the genetic background of the breeding material (Fig.…”
Section: Molecular Studies In Chillimentioning
confidence: 99%